Feasibility of a Collaborative, Prospective Interdisciplinary Review and Pharmacy-Based Dispensing Process for Prothrombin Complex Concentrate. Issue 5 (May 2018) - Stratton, Maria; Grgurich, Philip; Heim, Kurt; Mackey, Sandra; Burns, Joseph D.
Background: Therapeutic options for rapid reversal of vitamin K antagonist therapy include 4-factor prothrombin complex concentrate (PCC4) and fresh frozen plasma (FFP). These agents have unique requirements for preparation, potential adverse effects, and cost-effectiveness considerations.Objective: To retrospectively assess whether our process for collaborative prospective review and pharmacy preparation facilitates timely and safe warfarin reversal with PCC4 as compared with FFP and to compare effectiveness and safety of the agents in practice.Methods : We performed a retrospective, single-center, before and after cohort study of patients requiring warfarin reversal for life-threatening bleeding or urgent invasive procedures over an 18-month period. The primary end point was time from ordering of reversal agent to administration. Secondary end points measured time to therapeutic effect and rates of adverse events.Results : Of 98 patients studied, 72 received FFP, and 26 received PCC4. The median times from ordering to administration of FFP and PCC4 were 69 and 44 minutes, respectively ( P = 0.015). Median time from ordering to end of infusion was significantly shorter for PCC4 compared with FFP (54 vs 151 minutes, respectively; P < 0.0001). In all, 72% of PCC4 patients and 28% of FFP patients achieved the goal international normalized ratio (INR) of ≤1.4 at the first INR check ( P < 0.0001). Adverse reactions occurred in 4% of patients in each group.Conclusion : In routine clinical practice incorporating collaborative prospective review and dispensing from the institution's pharmacy, PCC4 was associated with faster administration, a higher rate of INR correction, and similar rates of adverse events compared with FFP.